Disaggregating the SWOT Analysis of Marine Renewable Energies - Goffetti, Giulia; Montini, Massimiliano; Volpe, Francesca; Gigliotti, Massimo; Pulselli, Federico M.; Sannino, Gianmaria; Marchettini, Nadia (Frontiers in Energy Research, 2018)
Energy transitions require strategic plans that minimize inefficiencies and maximize energy production in a sustainable way. This aspect is fundamental in the case of innovative technologies based on marine renewable energies. Marine renewable energies involve problems and advantages which imply a reconceptualization of marine space and its management. Through an holistic SWOT analysis the main strengths, weaknesses, opportunities and threats are highlighted in this paper, considering social, economic, legal, technological, and environmental dimensions. We disaggregate the SWOT analysis for marine renewable energy technologies in order to create an overview of pros and cons for every dimension and better identify specific hotspots and possible solutions in different fields.